Pengaruh Kecerdasan Emosional Terhadap Perolehan Belajar Matematika Ranah Kognitif Dan Afektif - Michael; Yulis Jamiah; Revi Lestari Pasaribu (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to determine the effect of emotional intelligence on cognitive and affective mathematics learning outcomes. This quantitative research uses an ex post facto design. The population was 10th-grade students at SMK Mandiri Pontianak, with a sample of 35 students selected via purposive sampling. Data were collected using emotional intelligence questionnaires, affective questionnaires, and cognitive achievement tests. Data analysis utilized simple linear regression and Multivariate Multiple Regression (MMR). The results showed that emotional intelligence significantly contributed 16.9% to cognitive learning outcomes and 34.2% to affective learning outcomes. Simultaneously, emotional intelligence significantly influences both domains. It is recommended that educators manage students' emotional intelligence to optimize the overall learning process.